Eco-friendly preparation of electrically conductive chitosan - reduced graphene oxide flexible bionanocomposites for food packaging and biological applications - Barra, Ana (2020)
Electrically conductive materials have been highlighted in the biomedical and food packaging areas. Conventional electrically conductive polymers have limited biodegradability and biocompatibility and should be replaced by suitable biomaterials. Herein, electrically conductive bionanocomposites of chitosan and reduced graphene oxide were produced by a green methodology. The reduced graphene oxide was hydrothermally reduced in the presence of caffeic acid and was dispersed into chitosan. The final bionanocomposites achieved an electrical conductivity of 0.7 S/m in-plane and 2.1 × 10−5 S/m through-plane. The reduced graphene oxide promoted a great enhancement of antioxidant activity and a mechanical reinforcement of chitosan matrix, increasing the tensile strength and decreasing the water solubility. The electrical conductivity, mechanical properties and antioxidant activity of the bionanocomposites can be tuned according to the filler content. These active bionanocomposites, prepared using a green methodology, revealed good electrical and mechanical properties, which make them promising materials for food packaging and biological applications.